Strategies for improving the efficacy of donor lymphocyte infusion following stem cell transplantation. (January 2016) - Stamouli, Maria; Gkirkas, Konstantinos; Tsirigotis, Panagiotis
Donor lymphocyte infusion (DLI) is an effective immunotherapeutic approach with significant activity in the treatment and prevention of relapse after allogeneic stem cell transplantation. DLI is associated with significant toxicity mainly due to graft-versus-host disease. Moreover, DLI does not produce durable responses in aggressive malignancies like acute leukemia. Improvement in DLI efficacy requires dissociation of graft-versus-leukemia effect from graft-versus-host disease. Minor histocompatibility antigens with tissue restriction and leukemia or tumor-associated antigens represent ideal antigenic targets. A brief overview of the existing methods of DLI administration is the topic of this article. T cells transduced with genes encoding for T-cell receptors with reactivity against minor histocompatibility antigens or leukemia-associated antigens is a promising option.